Late Holocene increase in sea ice extent in fjords of the Vestfold Hills, eastern Antarctica - McMinn, A (Antarctic Science, 2000)
Sediment cores from Abel and Platcha Bays, in the Vestfold Hills, east Antarctica, contain evidence for a local late Holocene increase in fast ice extent and a possible ice cap retreat at approximately 1750 yr BP, a similar time to the Chelnock Glaciation. Prior to this time both bays experienced periods of isolation that lead to changes in their diatom flora, C:N ratio, percentage of biogenic silica and total organic carbon. Three new diatom indices are proposed; the fast ice index, based on the proportion of fast ice taxa present, the benthic index, based on the proportion of benthic taxa and the snow index, based on the proportion Berkelaya adeliense and Thalassiosira australis. These indices show strong relationships with the percentage of biogenic silica, total organic carbon and percentage sand. A weak relationship exists between the fast ice index and 13C and no relationship with the C:N ratio.